Leveraging the potential of social media: Unveiling the influence of customer-generated photos on customer behavior - Asif Ali Safeer; Muhammad Abrar; Yewang Zhou (PLoS ONE, 2025)
Recent research shows that social media has enormous potential for customers and enterprises, but this potential has been largely untapped. This study investigates the influence of customer-generated photos on social media to drive customer visit intentions via the argument quality of online reviews, including perceived informativeness and persuasiveness, by integrating the direct and moderating effects of brand social media visual communication and controlling customer demographics such as gender, age, and income in the context of restaurants. This study collected 1,137 responses from different customers through an online survey. After carefully filtering data, 980 customer responses were analyzed using structural equation modeling. This study discovered that customer-generated photos significantly influenced perceived informativeness, persuasiveness, and customer visit intentions. Likewise, perceived informativeness and persuasiveness directly and indirectly contributed to increased customer visit intentions. In addition, brand social media visual communication directly influences to drive customer visit intentions toward restaurants. This study offers fresh insights for restaurant marketers to devise innovative marketing strategies to influence customer behavior toward eateries. Employing a social media ecosystem, this study contributes to the heuristic-systematic and elaboration likelihood models by examining consumer behavior in the hospitality industry.